YouTube for Assisting Autonomous Deaf English Learners in Mastering EFL - Angela Bayu Pertama Sari (JELLT (Journal of English Language and Language Teaching), 2022)
Teaching English to students with special needs has been a concern in Indonesia. However, there were still some limitations in the practice of teaching and learning in class. Thus, this research tried to portray the use of YouTube to improve the quality of English learning outside the classroom. This research attempted to depict YouTube's use to assist autonomous deaf learners in mastering English as a foreign language. This research utilized case study research and thematic data analyses. The subject of the research was one autonomous deaf English learner. The data collecting technique was a written interview through an online chat application. The first result of the research pointed out that there were four learning manners of the autonomous deaf learner in optimizing the English learning process through YouTube, namely using the caption feature, backward feature, comment section, and google translate to learn more about English. The second result revealed that the autonomous deaf English learner obtained three insights from the learning process through YouTube: grammar knowledge, vocabulary, and general knowledge, particularly about knitting. Finally, it may be concluded that the YouTube features that served captions, backward buttons, and comment sections became the paramount factors for supporting the learning autonomy of the deaf learner in mastering English as a foreign language.